Transformational Leadership And Psychological Empowerment In Malaysian Public Universities: A Review Paper - Mohammed Abdulrab; Qais Almaamari; Ali Al-Tahitah; Abdul Rahim Zumrah (Indian Institute for Secondary & Technical Education, 2024)
Non-Indexed Publication